Bivalve borings in Lower Jurassic Lithiotis fauna from northeastern Italy and its palaeoecological interpretation. (3rd October 2017) - Bassi, Davide; Posenato, Renato; Nebelsick, James H.; Owada, Masato; Domenicali, Enrica; Iryu, Yasufumi
Abstract: Random shell sections of the Pliensbachian (Early Jurassic) larger bivalve Opisoma from columns within the Main Post Office building of Ferrara, northern Italy, have been discovered to bear neat clavate-shape boreholes. These boreholes belong to the ichnogenus Gastrochaenolites Leymerie and represent bivalve borings. Opisoma is a subordinate component of the Lithiotis fauna characterised by aberrant shells thriving in tropical lagoonal settings which were widespread throughout the Tethyan and Panthalassa coasts. Although the Lithiotis fauna is well known in the palaeontological literature, no bivalve boring have been so far been formally described. The uniqueness of the morphology, size and substrate of these borings merits the designation of the new species Gastrochaenolites messisbugi ichnosp. nov. which thereby represents the first ichnospecies described from this fauna. The morphology of the boreholes and the included bivalves allows the boring activity to be ascribed to a mytilid bivalve. Palaeoecological and taphonomic analyses allowed the presence of the boreholes to be correlated to the Opisoma mode of life (epifaunal, free-living form) as well as to generally low sedimentation rates and seasonal mesotrophic conditions during an overall oligotrophic regime. http://zoobank.org/urn:lsid:zoobank.org:act:CCF77B32-D459-4305-BC86-93F228852E50